Apakah Social Support Memengaruhi Perasaan Malu ? : Tinjauan Pada Dewasa Muda yang Menganggur - Juniarly, Amalia; Anjani, Dewi (Merpsy Journal, 2024)
Unemployment in Indonesia is still high, this is due to an imbalance between the number of job vacancies available and the number of job applicants. The consequences of being unemployed have an impact on a person's of shyness. The aim of this research is to determine the role of social support and each type (emotional support, instrumental support, informational support and companionship support) on shyness in unemployed young adults. The hypotheses in this research consist of a major hypothesis, namely that there is a role of social support in shyness. The minor hypothesis is that there is a role for emotional support, instrumental support, informational support, and companionship support in shyness. The sampling technique used was purposive sampling. The measuring instrument used is a scale compiled by the researcher himself by referring to the symptoms of shyness from Henderson and Zimbardo (1998) and referring to the types of social support from Sarafino and Smith (2011). Data analysis uses multiple regression analysis. The research results show that social support has a role in shyness in unemployed young adults. The results of this research also show that the types of social support, namely emotional support and informational support, have a negative and significant role in shyness, so the hypothesis is accepted. The types of social support, namely instrumental support and companionship support, do not play a role in shyness, so the hypothesis is rejected. Meanwhile, emotional support contributed to shyness by 19.5% and informational support by 12.93%.